AGENRE-PROJECT BASED APPROACH TO TEACHING WRITING BIOGRAPHICAL RECOUNT TEXT - Ekaningtias, Runi (2015)
This study reports on the investigation of a synthesis of Genre-based approach with Project-based Learning method and its implementation in teaching writing biographical recount text to thirty eight graders of one Islamic secondary school of Madrasah Tsanawiyyah in Cianjur.This study was intended to find out the values of the use of Genre-based approach synthesised with Project-based Learning in helping students develop their ability to write biographical recount text.This study employed a qualitative research design, embracing characteristics of a case study. The study was carried out within seventeen meetings. It covered eleven meetings of the first teaching cycle, five meetings of the second teaching cycle, and one meeting of focus-group interview.The study involved three types of instruments, including classroom observations, students' biographical recounttexts, and focus-group interview.This study revealed that, to most extent, genre-project based approach was found to be helpful to develop students' ability to write biographical recount text. In addition, from the interview, it was shown that the teaching program has motivated the learners to produce more texts and to perform in another English project. However, it was identified that the teaching and learning process should be continued, the editing process should be conducted in a longer period, and the students needed to be guided more in English biographical writing. Keywords: Genre-based approach, project-based learning, biographical recount text, writing Penelitianinimelaporkanmengenaiinvestigasisebuahsintesisantarapendekatan Genre-based denganmetode Project-based Learning danimplementasinyadalampengajaranmenulisteks recount biografiterhadaptigapuluhsiswakelasdelapan di salahsatusekolah Madrasah Tsanawiyyah di Cianjur. Penelitianinibertujuanuntukmendapatkannilaidaripenggunaanpendekatan Genre-based yang di sintesiskandengan Project-based Learning dalammembantusiswauntukmengembangkankemampuanmenulismerekadalammenulisteks recount biografi. Penelitianinimenggunakandesainpenelitian qualitative, mencakupsebuahstudikasus.Penelitianiniberlangsungselamatujuhbelasminggu. Hal itumencakupsebelaspertemuandaripengajaranpadaputaranpertama, limapertemuanpadapengajaranputarankedua, dansatupertemuanuntuk focus grup interview. Penelitianinimenggunakantigajenis instrument, yaituobservasikelas, teks recount biografisiswa, dangrup interview. Hasildaripenelitianmenunjukanbahwa, dalambeberapahal, pendekatan genre-project based dapatmembantusiswadalammengembangkankemampuanmenulisteks recount biografi. Sebagaitambahan, dalamsesiwawancara, program pengajaran yang dilakukantelahmemotivasisiswauntukmemproduksiberbagaijenisteksdanmembuatpertunjukandalamproyekBahasaInggrislainnya.Namundemikian, dapat di identifikasibahwa proses pengajarandanpembelajaran yang diselenggarakanseharusnyadilanjutkan, proses edit jugaseharusnyadilakukandenganwaktu yang lebih lama, danparasiswaperludibimbinglebihdalammenulisbiografi.